THE EFFECT OF CTL (CONTEXTUAL TEACHING AND LEARNING) ON STUDENTS’ SPEAKING DESCRIPTIVE TEXT ABILITY (A Study at the Eigth Grade of MTs Jabalul Madaniyah in 2020/2021 Academic Year) - Harahap, Nira (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Absract : The purposes of this research are to know: 1) The application of CTL (Contextual Teaching and Learning) in teaching speaking descriptive text ability, 2) Students’ speaking descriptive text ability before and after using CTL (Contextual Teaching and Learning), 3) Is there any significant effect of using CTL (Contextual Teaching and Learning) at the eigth grade of MTs Jabalul Madaniyah.in order to achieve the purpose of the research, the writer carried the quantitative approach by using experimental research method with onegroups pre-test and post-test design.The population of this research is the eigth grade students of MTs Jabalul Madaniyah which consists 83 students. The writer used purposive non probability sampling to get sample that consists to 33 students. The data was collect by using observation sheet and oral test.The result application of CTL (Contextual Teaching and Learning) is 3.6, it is categorized “very good”. The result before using CTL (Contextual Teaching and Learning) is 43.75, it is categorized “ fail”. Then, the result after using CTL (Contextual Teaching and Learning) is 75.90, it is categorized “good”. The result of ttest is 21.88 and t table is 2.04. It means that there is significant effect of using CTL (Contextual Teaching and Learning) on students’ speaking descriptive text ability at the eigth grade of MTs Jabalul Madaniyah in 2020/2021 Academic Year. KeyWords : CTL (Contextual Teaching and Learning), Speaking Descriptive Text Ability Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui: 1) Penerapan CTL (Contextual Teaching and Learning) dalam pembelajaran kemampuan berbicara teks deskriptif, 2) Kemampuan berbicara teks deskriptif siswa sebelum dan sesudah menggunakan kemampuan CTL (Contextual Teaching and Learning), 3) Apakah terdapat pengaruh yang signifikan penggunaan CTL (Contextual Teaching and Learning) di kelas VIII MTs Jabalul Madaniyah. Untuk mencapai tujuan penelitian, peneliti melakukan pendekatan kuantitatif dengan menggunakan metode penelitian eksperimental dengan one-group pre-test dan post-test design. Populasi penelitian ini adalah siswa kelas VIII MTs Jabalul Madaniyah yang berjumlah 63 siswa. . Penulis menggunakan purposive non probability sampling untuk mendapatkan sampel sebanyak 33 siswa. Pengumpulan data dilakukan dengan menggunakan lembar observasi dan tes lisan. Hasil penerapan CTL (Contextual Teaching and Learning) adalah 3,6 dikategorikan “sangat baik”. Hasil sebelum menggunakan CTL (Contextual Teaching and Learning) adalah 43,75, dikategorikan “gagal”. Kemudian hasil setelah menggunakan CTL (Contextual Teaching and Learning) adalah 75,90 dikategorikan “baik”. Hasil uji ttest diperoleh nilai 21.88 dan ttabel 2.04. Artinya terdapat pengaruh yang signifikan penggunaan CTL (Contextual Teaching and Learning) terhadap kemampuan teks deskriptif berbicara siswa kelas VIII MTs Jabalul Madaniyah Tahun Ajaran 2020/2021 Kata Kunci :CTL (Contextual Teaching and Learning), Kemampuan Berbicara Descriptif Teks